👤

restrânge expresiile algebrice următoare, folosind formula
[tex] {a}^{2} + {ab}^{2} + {b}^{2} = {(a + b)}^{2} [/tex]
a)
[tex] {x}^{2} + 2x + 1[/tex]
b)
[tex] {x}^{2} + 4x + 4[/tex]
c)
[tex] {x}^{2} + 6x + 9[/tex]
d)
[tex] {x}^{2} + 10x + 25[/tex]
e)
[tex] {x}^{2} + 12x + 36[/tex]



Răspuns :

Răspuns:

Ai rezolvarea mai jos !

Explicație pas cu pas:

a) x² + 2x + 1 = ( x + 1 )² , unde a = x , iar b = 1

b) x² + 4x + 4 = ( x + 2 )² , unde a = x , iar b = 2

c) x² + 6x + 9 = ( x + 3 )² , unde a = x , iar b = 3

d) x² + 10x + 25 = ( x + 5 )² , unde a = x , iar b = 5

e) x² + 12x + 36 = ( x + 6 )² , unde a = x , iar b = 6.

#copaceibrainly